Penambahan Limbah Organik dalam Pakan untuk Meningkatkan Produksi Telur Burung Puyuh: Literature Review - A R R Agus (PETERPAN (Jurnal Peternakan Terapan), 2023)
Feed is a very important success factor in quail farming. Appropriate feeding can increase the production of quail eggs which are useful for meeting the protein consumption of today's society. Many researchers have tested the use of ratios combined with various kinds of existing organic waste. It aims to find alternative ratios that are useful to reduce the cost of expensive feeds but still produce quail that is productive in terms of laying eggs. This researcher aims to find alternative food in the ratio in the form of organic waste that is useful for increasing the production of quail eggs. This research article uses searches with certain keywords in the last 10 years. The results obtained from 8 articles related to the addition of organic waste in feeds to increase the production of quail eggs. The results of the literature review showed that from 8 articles showed that there was no effect of adding organic waste in the feed to increase quail egg production. Recommendations from the literature review can be used as a reference for future research to find other alternatives in feed to increase quail egg production.